Development and validation of a questionnaire for measuring drug-induced nausea - Prokić, Andjelka; Janković, Slobodan M. (Vojnosanitetski pregled, 2021)
Background/Aim. There are several questionnaires for measuring intensity of nausea after drug administration, but they are either too settings specific (like those measuring chemotherapy-induced nausea), or they were not properly tested for reliability and validity. The aim of this study was to develop and validate a reliable instrument that can measure drug-induced nausea. Methods. The cross-sectional study for assessing reliability and validity of a questionnaire was performed. The questionnaire with 5 items and answers according to the Likert’s scale was developed during two brainstorming sessions of the research team. Its reliability, validity and temporal stability were tested on the sample of 128 outpatients taking iron salts orally. Results. The final version of the Drug-Induced Nausea Scale (DINS) with 5 items showed excellent reliability, both when rated by the investigators (Cronbach’s alpha 0.892) and by the patients themselves (Cronbach’s alpha 0.897). It was temporally stable, and both divergent and convergent validity tests had very good results. Factorial analysis revealed only one factor, which means that the whole scale is measuring only one phenomenon, intensity of nausea, as was originally intended. Conclusion. The DINS is reliable and valid instrument for measuring intensity of drug-induced nausea. Identification of patients with high intensity of drug-induced nausea by this questionnaire will help prescribers to decide whether the therapy should be stopped or the patient switched to less emetogenic therapy.